2003
DOI: 10.1021/jf034310n
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of [14C]Imidacloprid in Sunflowers (Helianthus annuus L.) following Seed Treatment

Abstract: Imidacloprid, a neonicotinic insecticide, has been used as a seed dressing (Gaucho) to protect crops against soil and aerial insects. However, French beekeepers observed abnormal behavior of bees foraging on sunflowers and suspected a link between the imidacloprid seed treatment and the observed bee syndrome. This work studies the distribution of [(14)C-imidazolidin]imidacloprid (1 mg/seed) in three stages of Gaucho-treated sunflowers grown in an outdoor lysimeter. Plants absorbed <10% of [(14)C]imidacloprid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 17 publications
4
74
1
1
Order By: Relevance
“…Increased probability of Nosema infection was reported in bees that consumed pollen with a higher fungicide load (Pettis, Lichtenberg, Andree, Stitzinger, & Rose, 2013). Likewise, the residues of insecticide imidacloprid in nectar and pollen at high levels may be dangerous to bees (Laurent & Rathahao, 2003;Chauzat et al, 2006). Widespread losses of colonies in France is due to imidacloprid (Laurent & Rathahao, 2003).…”
Section: Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased probability of Nosema infection was reported in bees that consumed pollen with a higher fungicide load (Pettis, Lichtenberg, Andree, Stitzinger, & Rose, 2013). Likewise, the residues of insecticide imidacloprid in nectar and pollen at high levels may be dangerous to bees (Laurent & Rathahao, 2003;Chauzat et al, 2006). Widespread losses of colonies in France is due to imidacloprid (Laurent & Rathahao, 2003).…”
Section: Pesticidesmentioning
confidence: 99%
“…Likewise, the residues of insecticide imidacloprid in nectar and pollen at high levels may be dangerous to bees (Laurent & Rathahao, 2003;Chauzat et al, 2006). Widespread losses of colonies in France is due to imidacloprid (Laurent & Rathahao, 2003). Similarly, other pesticides "acaricides" have also been found harmful for bees' health (Harz, Muller, & Rademacher, 2010).…”
Section: Pesticidesmentioning
confidence: 99%
“…Residues of such insecticides can be translocated to various plant parts (Dively and Kamel 2012;Goulson 2013). For example, residues of imidacloprid have been found at 13 ppb in sunflower pollen following its application as a seed treatment (Laurent and Rathahao 2003). Chlorantraniliprole and thiamethoxam represent two systemic insecticides used in seed treatments, belonging to two different groups, diamides and neonicotinoids, respectively.…”
mentioning
confidence: 99%
“…Imidacloprid residues have been found at concentrations of up to 13 ng in sunflower plants (Laurent & Rathahao, 2003). Chauzat et al (2006) identified 36 different types of residues in pollen loads in apiaries of France.…”
Section: Introductionmentioning
confidence: 99%